PENGARUH KOMPLEKSITAS PERUSAHAAN, KOMITE AUDIT, DAN FINANCIAL DISTRESS TERHADAP AUDIT REPORT LAG - Evans Trias Genesius (2023)
This study aims to empirically prove the effect of Company Complexity, Audit Committee, and Financial Distress on Audit Report Lag. The research population used in this research is energy sector companies listed on the Indonesia Stock Exchange in the 2020-2022 period. Samples were taken using purposive sampling method by obtaining a sample of 55 companies from 80 companies. This study uses multiple linear regression analysis as a data analysis technique using STATA Version 14 software. The results show that company complexity and audit committees have no significant effect on audit report lag, while financial distress has a negatively significant effect on audit report lag.